Forest Fires: Why the Large Year-to-Year Variation in Forests Burned? - Jay Apt; Dennis Epple; Fallaw Sowell (Center for Economic Studies and ifo Institute (CESifo), 2023)
Quantifying factors giving rise to temporal variation in forest fires is important for advancing scientific understanding and improving fire prevention. We demonstrate that eighty percent of the large year-to-year variation in forest area burned in California can be accounted for by variation in temperature, precipitation, housing construction, electricity transmission, and ocean surface temperatures in the North Atlantic, North Pacific, and Equatorial Pacific. California is of particular interest because of its large acreage burned and proximity of fires to human populations. We believe our model is the first unified treatment of climatic factors and human activities that affect forest area burned.
Keywords: H; Q20; Q50; 330; forest fires; climate; human activities; ocean surface temperatures